Effects of personalized time-trial goal setting on swimming performance and psychological profiles in competitive swimmers - Ferchichi, N.; Amara, S.; Aouani, H.; Bouassida, A.; van den Tillaar, R. (Frontiers in Sports and Active Living, 2026)
Swimming performance results from a complex interaction between physiological and psychological factors. The use of specific goal-setting has emerged as a promising psychological strategy; however, its influence on emotional states and time-based performance in real competitive conditions remains insufficiently documented. The aim of this study was to investigate the effect of setting a specific time-based performance goal on 100-m freestyle performance and psychological states in competitive swimmers. Twenty-four male swimmers (15.2 ± 0.8 years) were randomly assigned to an experimental group (n = 12) or a control group (n = 12). The experimental group received an individualized performance goal based on the goal-range setting model, whereas the control group was instructed to "perform at their best." All swimmers completed an 8-week standardized training program. Performance in the 100-m freestyle and psychological states (POMS) were assessed pre- and post-intervention. The mixed ANOVA revealed a significant main effect of time on performance (p < 0.001) and a significant Time × Group interaction (p = 0.004). Both groups improved following the intervention; however, the improvement was greater in the experimental group (4.3% vs. 2.5%). Regarding psychological variables, a significant main effect of time was found for total mood disturbance (p < 0.001), along with a significant Time × Group interaction (p < 0.001). Total mood disturbance increased in both groups, but to a greater extent in the experimental group (47.1% vs. 19.1%). All POMS subscales demonstrated significant effects of time and interaction, except for fatigue (p = 0.143). Post hoc analyses showed significantly greater increases in all affective states in the experimental group, while fatigue did not differ significantly between groups (13.7% vs. 9.3%). Implementing an individualized time-based performance goal was associated with improved swimming performance; however, it was also accompanied by a substantial emotional cost, reflecting an imbalance between performance demands and available psychological resources. The use of individualized goals should be coupled with structured psychological monitoring, including regular mood profiling, emotional regulation strategies, and progressive co-construction of the performance target. A gradual implementation approach appears necessary to optimize performance gains while preserving athlete well-being.